2019
DOI: 10.1177/2050640619852255
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the mucosa‐associated microbiota along the entire gastrointestinal tract of human individuals

Abstract: Background Homeostasis of the gastrointestinal tract depends on a healthy bacterial microbiota, with alterations in microbiota composition suggested to contribute to diseases. To unravel bacterial contribution to disease pathology, a thorough understanding of the microbiota of the complete gastrointestinal tract is essential. To date, most microbial analyses have either focused on faecal samples, or on the microbial constitution of one gastrointestinal location instead of different locations within one individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 24 publications
11
80
0
Order By: Relevance
“…We confirmed that α‐diversity was lower in the duodenal MAM of uninfected H pylori patients than the diversity reported from the lower gastrointestinal tract; Shannon's index 4.68 vs 6, respectively 56 . In a recent report that described the fecal α‐diversity in a similar population to the one studied here, Shannon index was 6.31 in subjects without H pylori infection 57 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We confirmed that α‐diversity was lower in the duodenal MAM of uninfected H pylori patients than the diversity reported from the lower gastrointestinal tract; Shannon's index 4.68 vs 6, respectively 56 . In a recent report that described the fecal α‐diversity in a similar population to the one studied here, Shannon index was 6.31 in subjects without H pylori infection 57 .…”
Section: Discussionsupporting
confidence: 86%
“…Kashiwagi et al 66 indicate that duodenum Fusobacteria were more abundant than Actinobacteria. Other authors indicate that in descending order of abundance, the predominant phyla in the small intestine are Proteobacteria, Firmicutes, Bacteroidetes, Fusobacteria, and Actinobacteria 56,67 . Regarding duodenal microbiome composition at the genera level, the most frequent taxa identified here were Ralstonia , Streptococcus, Pseudomonas , Burkholderia‐Caballeronia‐Paraburkholderia , Haemophilus, Herbaspirillum, Neisseria, and Veillonella .…”
Section: Discussionmentioning
confidence: 59%
“…The upper GIT microbiota in non-coprophagic mice was dominated by Lactobacilli ( Fig. 3c), known to be a prominent microbial taxon in human small intestine microbiota [3,40,41]. Importantly, the compositional analysis showed that the single TC-F mouse that had high microbial loads in its stomach and small intestine had a microbial composition in those segments of the GIT similar (i.e., dominated by Lactobacillales) to all other TC-F mice, and very distinct from all coprophagic mice (Fig.…”
Section: Self-reinoculation Substantially Alters the Microbiota Compomentioning
confidence: 99%
“…HMA mice have emerged as an important research model for dissecting the mechanistic connection between the gut microbiota and the host phenotype in health and disease, even though the field acknowledges its limitations [132,133]. Compositional differences between the small intestine and large intestine microbiomes in primates and humans [12,40,41] appear to be more substantial than those reported for laboratory mice [35,130]. Our study emphasizes that the compositional similarity between small and large intestine microbiota in conventional laboratory mice can be a result of self-reinoculation with fecal flora.…”
Section: Relevance Of Mouse Models In Human Microbiota Researchmentioning
confidence: 99%
“…Firmicutes covers the majority of butyrate-producing bacteria in human bacterial communities, and is known for its function in transforming undigested proteins and carbohydrates into acetic acid, and producing energy for the organism of host [12]. Meanwhile, the crucial short-chain fatty acids (SCFAs) butyrate participates in activating multiple physiological signal pathways, such as anti-inflammatory activities, and the differentiation and proliferation of regulatory T cells [13,14]. Under this circumstance, the lower abundance of Firmicutes in present study may be more reasonable.…”
Section: Discussionmentioning
confidence: 99%